Marriage Of Married Couples Who Have Been Rejected 3 Without Doing Muhallil Perspective Of Imam Shafi'I (Case Study Of Kelurahan Perjuangan, Teluk Nibung District, Tanjungbalai City) - Arma, Hilmia; Mukhsin, Abd (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The mentality law of wives according to Jumhur Ulama is mubah but the action is better avoided. Shafi'iyah and Hanablah scholars thought that the law of talaq was sometimes obligatory, sometimes haram and sometimes sunnah. Muhallil is the party of a man who marries a woman who is triple rejected by her husband so that the husband can initially return to the wife. In this muhalil marriage, a matter arises, namely engineering when the ex-husband or wife wants to return to the ex-husband, they do a serial marriage without doing the muhallil marriage first by the wife. The type of research used is empirical normative research. Based on the information achieved in primary information and secondary information. In this study, the registrar collected information through interviews. After obtaining the information needed, that the author analyzes qualitatively juridically. His research was conducted in Kelurahan Perjuangan, Teluk Nibung District, Tanjungbalai City. From the results of research conducted in Kelurahan Perjuangan Teluk Nibung District, Tanjungbalai city, information was obtained that there were six married couples who married their wives who had been triple rejected, the wife did not do Muhallil first. The results showed that the marriage of husband and wife who had been rejected was carried out in serial or unwritten marriages at the Office of Religious Affairs..